The saying of Bukhari (He disagrees with his hadith) A critical study in his book The Middle History - Mohammed, Ibrahim; Mohammed, Aboothar (Islamic Sciences Journal, 2023)
Al-Bukhari gives several words to the narrators in his book Al-Tarikh Al-Awsat, including the word: (he contradicts in his hadith), that is, in his hadith he contradicts hafez, and the contradiction among the narrators is no more than two issues. Either the narrator is weak or trustworthy, and if he is weak and contradicts trustworthy or Hafiz, then his hadith is objectionable, and if he is trustworthy and disagreed with the trustworthy, or who is more trustworthy than him, then his hadith is odd. Al-Bukhari has given this word to seven narrators. The current study shows that all of them are poor and they have contradicted the more trustworthy hafiz.